The Suez crisis - Fiscus, James W. (New York, N.Y. The Rosen Publishing Group, INC, 2004)
Examines the history behind Egypt's push for control of the Suez Canal and the battle waged against Britain, France, and Israel, and includes biographical notes on leaders and a look at the effects of the crisis.
Background for war : why Suez? -- Conspiracy for war -- The war -- Imposed peace and impact of the war.
Includes bibliography references and Index
Keywords: Sinai Campaign -- Causes -- Juvenile literature -- 1956; Egypt -- History -- History -- Intervention -- 1956; Israel -- France -- Foreign relations -- Juvenile literature; France -- Israel -- Foreign relations -- Juvenile literature; Israel -- Great Britian -- Foreign relations -- Juvenile literature; Great Britain -- Israel -- Foreign relations -- History; Suez Canal (Egypt) -- Juvenile literature